POTENSI PENGEMBANGAN PETERNAKAN BABI BERDASARKAN ANALISIS LOCATION QUOTIENT - Nautus Stivano Dalle; Hendrikus Demon Tukan; Elisabeth Yulia Nugraha; Wigbertus Gaut Utama (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2023)
The purpose of this study is to determine areas in Manggarai that have potential in pig development. The method used in this study is secondary data observation of Manggarai Regency and will be analyzed using Location Quotient (LQ) analysis. The results showed that the areas that received LQ 1 scores were Satar Mese, West Satar Mese, Wae Ri'i, Cibal and West Reok districts. This means that the region has not been able to meet the needs of its own territory and is still importing from other regions. While the sub-districts that received LQ 1 scores were North Satar Mese, Langke rembong, Ruteng, Lelak, North Rahong, West Cibal and Reok. This means that the pig farming sector is able to meet the needs of its own region and is also able to export outside the region. Manggarai District, North Satar Mese, Langke Rembong, Ruteng, Lelak, North Rahong, West Cibal and Reok are districts with superior communities in the form of livestock